Analysis of HOTS-Based TPACK Ability Based on Self-Assessment of Teacher Professional Education Students - Atmojo, Idam Ragil Widianto; Isnantyo, Fajar Danur; Muzzazinah, Muzzazinah; Triastuti, Rini; Ekawati, Elvin Yusliana; Sukarno, Sukarno (Mimbar Sekolah Dasar, 2025)
In the era of 21st-century education, mastery of Technological Pedagogical Content Knowledge (TPACK) is not enough without having higher-order thinking skills (HOTS). This study aimed to analyze HOTS-based TPACK ability in the field of Elementary School Teacher Education (ESTE). This study employed a quantitative descriptive approach with a survey design and data collection through self-assessment instruments. 1644 ESTE students of Teacher Professional Education (TPE) who filled out the instrument from various regions in Indonesia. The students consisted of 94 prospective teachers (Pre-service teachers of TPE) and 1550 TPE students who had become teachers (In-service teachers of TPE). The results showed that ESTE students of TPE showed very good mastery of HOTS-based TPACK. In the Content Knowledge aspect, 90% of students were categorized as having a high level of competence, indicating strong mastery. The ability to solve problems (53.7%) and evaluate student understanding (55.3%) were categorized as medium. In the Pedagogical Knowledge domain, the ability to manage classrooms (69.2%) and select appropriate learning strategies (66.5%) fell into the high category. For Technological Knowledge, 76.2% of students demonstrated a high ability to utilize technology effectively, although 16.9% still had difficulties in evaluating software, which was classified as low. Meanwhile, in the integrative TPACK aspect, 62.8% of students were in the high category in assessing student learning outcomes using a HOTS-based approach. In conclusion, ESTE students of TPE showed very good mastery of HOTS-based TPACK competencies, with high abilities in content knowledge, pedagogy, and technology even though challenges in evaluating software remain to exist. This study implies the need to strengthen training in technology evaluation and the application of higher-order thinking skills to ensure comprehensive and sustainable TPACK competence in teacher education programs.